DAYA TETAS TELUR DAN TINGKAT KELANGSUNGAN HIDUP PADA BENIH IKAN MANFISH (Pterophyllum scalare) DI BPBAT MANDIANGIN - Eliyana, Widya; Herlina, Sri; Darmono, Darmono (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2025)
This study aims to analyze the level of corn farmers' participation in agricultural extension programs and the factors influencing it in the Porehu District. Employing a survey method with a descriptive analysis approach and a quantitative paradigm, the study involved 112 corn farmers as respondents. The results indicate that internal factors such as age, education, farming experience, income, and family dependents significantly impact farmers' participation in extension activities. Additionally, external factors including farmers' motivation, perception of extension, support for infrastructure, support from extension agents, and social environment support also significantly affect farmers' participation. These findings highlight the need to develop more effective and inclusive extension strategies and strengthen collaboration among the government, agricultural extension agents, farmer organizations, and other relevant stakeholders. Such efforts are expected to enhance farmer participation and the success of agricultural extension programs, ultimately positively impacting agricultural productivity and farmers' well-being.